Defining the Rearing Cage for Agriocnemis femina Damselfly (Odonata, Zygoptera, Coenagrionidae) - Janra, Muhammad Nazri; Herwina, Henny; Rahmayani, Hafizhah; Rahmawati, Lily; Sehati, Dika Putri; Fandesti, Shania Refka (Universitas Negeri Surabaya, 2020)
Rearing insects such as dragonflies and damselflies aim to gain uniform progeny that used for scientific purposes. In Indonesia, unfortunately, this rearing type is not yet common which suggests the time for its initiation. This study has objective to define the type of rearing cage for Agriocnemis femina damselfly (Odonata, Zygoptera, Coenagrionidae). It was conducted descriptively by using two smalls (9 x 13 x 23 cm), four medium (14 x 15 x 22 cm) and two larges (20 x 23 x 33 cm) size boxes as cage setups, with or without ornamental plants in it. The feeding was with limited (10-15 Drosophila flies provided per day) and unlimited provision. Data was analyzed descriptively. The results showed that A. femina lived normally, including eating and mating, within the large cage setup equipped with ornamental plants and unlimited feeding.